1968
DOI: 10.1246/bcsj.41.93
|View full text |Cite
|
Sign up to set email alerts
|

On the Structures of Alkali Polyaluminates

Abstract: Besides the so-called β-Al2O3 (R2O·11Al2O3; R=Na or K), there have been found two kindred compounds with approximate formulas, R2O·7Al2O3 (β′-Al2O3) and R2O·5Al2O3(β″-Al2O3). The structure determination of the latter two compounds was undertaken; the results are compared with the structure of β-Al2O3 in the present paper. These three structures are composed of spinel layers of the same configuration. The structures of β and β′ are very similar to each other, both equally bearing a layer-stacking according to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0
1

Year Published

1976
1976
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(52 citation statements)
references
References 0 publications
3
48
0
1
Order By: Relevance
“…The name fl"-alumina was first used by Yamaguchi & Suzuki (1968) for the compound NaEO.5A120 3 (or KzO.5AI203), because the crystal structure was substantially similar to that of fl-alumina, Na20.11Al20 3. It was later found that the fl"-alumina phase is considerably stabilized by the addition of a small amount of MgO and even single crystals have been prepared (Bettman & Peters, 1969;Kummer, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…The name fl"-alumina was first used by Yamaguchi & Suzuki (1968) for the compound NaEO.5A120 3 (or KzO.5AI203), because the crystal structure was substantially similar to that of fl-alumina, Na20.11Al20 3. It was later found that the fl"-alumina phase is considerably stabilized by the addition of a small amount of MgO and even single crystals have been prepared (Bettman & Peters, 1969;Kummer, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…-Beta alumina is used as the solid electrolyte in sodium/sulphur cells because of its exceptionally high Na + ion conductivity and negligibly low electronic conductivity [1][2][3][4][5]. It has the approximate formula Na 2 0.11 A1 2 0 3 and the structure (hexagonal, P6 3 /mmc) consists of layers of loosely bonded sodium ions between spinel-type blocks of aluminium and oxygen ions [6][7][8] as shown in figure 1. The mobility of the sodium ions within these planes is extremely high.…”
mentioning
confidence: 99%
“…This is preferred for use as an electrolyte because of its superior conductivity (~ 0.2 ohm -1 .cm" 1 at 350 °C compared to ~ 0.05 ohm -1 .cm -1 for the beta form). It has three spinel blocks per unit cell related by a threefold screw axis, compared to the two related by a twofold screw axis in beta alumina [8,9], and has a formula approximating to Na 2 0.5 A1 2 0 3 . This is a highly defective structure, the excess sodium relative to the beta alumina formula being compensated by aluminium ion vacancies.…”
mentioning
confidence: 99%
“…6). The β -and β "-alumina are non-stoichiometric compounds with hexagonal P6 3 /mmc (β -alumina) [130,131] and rhombohedral R3m (β "-alumina) [132,133] crystal structures, respectively. These structures have a twodimensional character.…”
Section: Methodsmentioning
confidence: 99%